Organic waste management in Canada: building a sustainable circular economy - Perger, Alja (Mednarodno inovativno poslovanje, 2019)
North America is a big consumer and consequently a big producer of waste. For the purpose of this project, we were primarily interested in collecting information in North America, focusing on Quebec primarily. The main research question was risen up duringthe fieldwork and assistance with the Canadian company. It clearly presents the enterprise readiness for obtaining a smart solution on organic/food waste problem. It is believed, how organic/food waste can be a resource of a high value. There is a capacity of creating a new path, where organic/food waste could become the important as plant/field nutrient supply. The circular approach to organic waste management is urgently needed in a way how the organic waste should be reduced and returned as productive resource input into our economy.
Keywords: circular economy; krožna ekonomija; organic waste; organski odpadki; pametna mest; recikliranje; recycling; smart cities; sustainability; trajnostni razvoj